1993
DOI: 10.1080/11250009309355803
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the rate of food vacuole formation during early clonal life ofParamecium primaurelia

Abstract: The rate of food vacuole formation was shown to vary in Paramecium primaurelia during early clonal life; under constant external environmental conditions, remarkable changes occurred in young cells within a few fissions. Studies on different life span clones showed an increased rate, sometimes gradual and constant, and sometimes interrupted by a decrease, followed first by a reduced, then by a constant number of food vacuoles per unit of time. The decrease in food vacuole number, which was not followed by reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Food vacuole formation in ciliates, including Paramecium, is sensitive to external environmental changes like temperature, pH, size and concentration of particles in the medium. Furthermore, Ramoino [20] described that in Paramecium primaurelia under constant conditions, food vacuole formation rate increased at different life span clones.…”
Section: Food Vacuole Formation In Paramecium Aureliamentioning
confidence: 99%
“…Food vacuole formation in ciliates, including Paramecium, is sensitive to external environmental changes like temperature, pH, size and concentration of particles in the medium. Furthermore, Ramoino [20] described that in Paramecium primaurelia under constant conditions, food vacuole formation rate increased at different life span clones.…”
Section: Food Vacuole Formation In Paramecium Aureliamentioning
confidence: 99%
“…Moreover, studies of phagocytosis in P. primaurelia showed that the food vacuole formation capacity varied during early clonal life [3] and that these changes were related to variations in protein synthesis [4]. It was, however, not explained why protein synthesis decreased despite the fact that the cell took up a large amount of precursors.…”
Section: Introductiollmentioning
confidence: 99%